2016
DOI: 10.1111/jeb.13009
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paternity in a wild population of Armadillidium vulgare: influence of infection with Wolbachia?

Abstract: Female multiple mating has been extensively studied to understand how nonobvious benefits, generally thought to be of genetic nature, could overcome heavy costs such as an increased risk of infection during mating. However, the impact of infection itself on multiple mating has rarely been addressed. The interaction between the bacterium Wolbachia and its terrestrial crustacean host, Armadillidium vulgare, is a relevant model to investigate this question. In this association, Wolbachia is able to turn genetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…An evaluation of long-term fitness should now be performed, as short-term deleterious effects of inbreeding for one breeding event are not necessarily associated with a decrease in lifetime reproductive success (Van de Casteele, Galbusera, Schenck, & Matthysen, 2003). Lifetime reproductive success should also be estimated for heterozygous females under more natural settings: mating strategies such as mate choice or multiple mating (Valette, Durand, Bech, Grandjean, & Beltran-Bech, 2017) might allow females to avoid or compensate for developmental failure or mortality due to inbreeding, so higher fecundity might result in higher fertility.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of long-term fitness should now be performed, as short-term deleterious effects of inbreeding for one breeding event are not necessarily associated with a decrease in lifetime reproductive success (Van de Casteele, Galbusera, Schenck, & Matthysen, 2003). Lifetime reproductive success should also be estimated for heterozygous females under more natural settings: mating strategies such as mate choice or multiple mating (Valette, Durand, Bech, Grandjean, & Beltran-Bech, 2017) might allow females to avoid or compensate for developmental failure or mortality due to inbreeding, so higher fecundity might result in higher fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this species displays both a monogamous mating system and biparental care (Linsenmair, 1984), as opposed to A. vulgare, which is characterized by a promiscuous mating system (Moreau & Rigaud, 2003;Valette et al, 2017) and nearly exclusive maternal care. It is then not surprising to observe different dispersal patterns across terrestrial isopods given the diversity in their ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Females in several terrestrial isopod species have been shown to reproduce with several males (Johnson, 1982;Sassaman, 1978;Moreau et al, 2002) and males can mate with several females (Moreau and Rigaud, 2003). In particular, A. vulgare presents a promiscuous system, as females can produce broods with up to 7 fathers in the wild (Valette et al, 2017). Due to small size and regular moulting, genetic tools appear particularly relevant to study dispersal in this species.…”
Section: Introductionmentioning
confidence: 99%